A NMR-based drug screening strategy for discovering active substances from herbal medicines: Using Radix Polygoni Multiflori as example. - Wan, Hong; Tian, Yafeng; Jiang, Haipeng; Zhang, Xu; Ju, Xiulian (Journal of Ethnopharmacology, 2020)
Herbal medicines have always been important sources for new drugs. And developing new drugs from traditional herbal medicine is currently still an effective way. However, screening for active substances from herbal medicines extracts has ever been a challenging topic, due to their intrinsic complexity. The herb Radix Polygoni Multiflori has been used as a tonic and an antiaging herb in Traditional Chinese Medicine. In clinical studies, the extract of Radix Polygoni Multiflori can improve hypercholesterolemia, atherosclerotic, diabetes and other diseases commonly associated with glycolipid metabolism, however, the molecular mechanisms of these actions are unknown. We devised a NMR-based drug screening strategy for discovering active substances from herbal medicines, using Radix Polygoni Multiflori as example to address such challenging topic, meanwhile, to explore molecular target of Radix Polygoni Multiflori's glycolipid metabolism benefit. Herbal medicines extracts were subjected to moderate separation to generate libraries of pre-purified subfractions, target protein was then added to each subfraction, and ligand-observed NMR experiments (line-broadening experiment, chemical shift perturbations measurements and saturation transfer difference spectrum) were performed, active substances identification and structural optimization were then accomplished using signals provided by ligand-observed NMR interaction detection and HPLC-SPE-NMR. The strategy was demonstrated by discovering an active component from extract of herb Radix Polygoni Multiflori , using human fatty acid binding protein 4 (FABP 4) as target protein. 2,4-dihydroxy-6-[(1E)-2-(4-hydroxyphenyl)ethenyl]phenyl-ß-D-glucopyranoside(TSG), the hit from one subfraction, has obvious interaction with target protein FABP 4 , due to FABP 4 is a potential therapeutic target for metabolic diseases such as diabetes and atherosclerosis, the screening result will give clue to the active component and molecular target of Radix Polygoni Multiflori 's glycolipid metabolism benefit. Besides, interaction information at atom level offered by ligand-observed NMR experiment would be valuable in the further stage of lead optimization. The devised NMR-based drug screening strategy can discover active substances from herbal medicines efficiently and precisely, meanwhile, can shed light on molecular mechanism of traditional usage of the herb. Image 1